The effects of herbs and fruits on leukaemia - Saedi, Tayebeh Azam; Md Noor, Sabariah; Ismail, Patimah; Othman, Fauziah (Hindawi Publishing Corporation, 2014)
In developing countries, herbal therapy is the first and basis form of treatment for most types of diseases. About 75–80% of the world’s population prefers herbal therapy as a major treatment due to its better adequacy and satisfactoriness, which enhance human body’s symmetry with minimal side effects. Fruits and plants have been presented from the past as promising tools in becoming a natural anticancer agents. Many of these plant extracts are currently used in cancer therapy and prevention. This review paper will particularly explore and emphasize on herbs and fruits used in the treatment of the leukaemia.